Phylum Arthropoda. In: Zhang, Z.-Q. (Ed.) Animal Biodiversity: An Outline of Higher-level Classification and Survey of Taxonomic Richness (Addenda 2013) - Zhang, Zhi-Qiang (Zootaxa, 2013)
The Arthropoda is here estimated to have 1,302,809 described species, including 45,769 fossil species (the diversity of fossil taxa is here underestimated for many taxa of the Arthropoda). The Insecta (1,070,781 species) is the most successful group, and it alone accounts for over 80% of all arthropods. The most successful insect order, Coleoptera (392,415 species), represents over one-third of all species in 39 insect orders. Another major group in Arthropoda is the class Arachnida (114,275 species), which is dominated by the Acari (55,214 mite and tick species) and Araneae (44,863 spider species). Other diverse arthropod groups include Crustacea (73,141 species), Trilobitomorpha (20,906 species) and Myriapoda (12,010 species).